O executivo de grandes corporações e sua opção de negócio próprio - Trevisan, Wilson de Paula (2012)
The decision of start a new business and the process of choosing what kind of business has been the subject of several studies. The relevance of this issue lies in its association with changes in the workplace. In the twenty-first century, the option of undertaking becomes increasingly a real and affordable way to generate income, occupation and work in a globalized environment in which large organizations reduce jobs, employment and shorter careers. In this context, we highlight the figure of seasoned middle-aged executive, fired from a large corporation, and sees the opening of the business itself an option to generate income and occupation. The objective is to understand the variables that influence the decision of when executives choose to start their own businesses and understand the reasons for the choice of business type and its selection criteria in light of the literature on entrepreneurship. This is a qualitative exploratory study that investigates how the dismissed executive develops its option to start a new business. To this end, there were five semi-structured interviews in which participants were asked to narrate their professional life stories and discuss issues related to their career development. The participants were five former executives who chose to mount his own business. The analysis of the transcript generated from the interview was performed using the method of analysis of the content. We performed the coding and categorization of the messages contained in the interviews, and information resulting from these procedures were the basis for the interpretation of results. Executives revealed that the decision process and choose the type of business to be started was, as the most important factors, the degree of mobility and accordingly, represented by the maximum time in an organization and the function or position most played in his career, together with the factors of attraction and financial comfort, ranging from Wright Mills executive typical described to the innovative businessman described by Joseph Schumpeter. From the results obtained, there were some thoughts that can serve as guidelines for future studies on this topic. These reflections have become in proposing a set of parameters, which aims to present the process of choosing the type of business of the former executive, through the scale and intensity of facts connected with its history of professional life, current situation and motivations